I Am Alfa and Omega: A Jewish-Christian Schema in the Manichaean Context Based on the Middle Iranian Documents in the Turfan Collection - Mohammad Shokri-Foumeshi (Religious Inquiries, 2018)
This paper will give an in-depth discussion of Jesus’ expression “I am Alpha and Omega” (Apocalypse of John = Revelation 1.8) and its influence on the Manichaean writings, on the one hand, and the reason for the division of Mani’s Living Gospel into twenty-two chapters, corresponding to the twenty-two letters of the Manichaean alphabet, on the other. The paper has explored all the related Jewish, Christian, and Manichaean texts available and strived to find out more about the reason for, and the origin of, this particular division. The deep connection between the word (or letters) and creation in Manichaean as well as in Jewish and Christian traditions seems to play an important role in this regard. The paper will answer many different, previously unanswered, questions and eventually propose a plausible resolution.